2003
DOI: 10.1080/00288233.2003.9513534
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the variation in fatty acid concentrations in lean beef from grass‐fed cattle in New Zealand and the implications for human health

Abstract: Lean beef from grass-fed cattle was analysed for fatty acid (FA) content to determine the between-animal variation and the effects of various traits on FA composition, and indices and FA ratios that have human health implications. In Experiment 1, samples were from three muscles from five bulls, five cows, and five heifers. In Experiment 2, samples were from the m. longissimus lumborum of 50 3 / 4 Jersey 1/ 4 Limousin and 50 3 / 4 Limousin 1/ 4 Jersey cattle, born over 2 years and sired by two bulls. The heife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
15
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 25 publications
(45 reference statements)
6
15
0
2
Order By: Relevance
“…These results are consistent with those of Peterson et al (2002) who found that, despite variations in diet, the ranking of dairy cows for CLA concentration in milkfat was maintained over the lactation. Breed and sire effects on CLA and TVA concentrations have been reported in beef, indicating that genotype can affect the concentrations of these FA (Knight et al 2003). The CLA concentration in milkfat from ewes of 1.5-2.6 g 100 g -1 TFA was similar to the values of 1.2-2.2 g CLA 100 g-1 TFA in the milkfat of New Zealand dairy cows fed grass (Kay et al 2002).…”
Section: Discussionsupporting
confidence: 48%
See 4 more Smart Citations
“…These results are consistent with those of Peterson et al (2002) who found that, despite variations in diet, the ranking of dairy cows for CLA concentration in milkfat was maintained over the lactation. Breed and sire effects on CLA and TVA concentrations have been reported in beef, indicating that genotype can affect the concentrations of these FA (Knight et al 2003). The CLA concentration in milkfat from ewes of 1.5-2.6 g 100 g -1 TFA was similar to the values of 1.2-2.2 g CLA 100 g-1 TFA in the milkfat of New Zealand dairy cows fed grass (Kay et al 2002).…”
Section: Discussionsupporting
confidence: 48%
“…Saponification of the lipids and methylation of the subsequent FA in milk, plasma, and lamb meat extracts, and the GLC analysis of the FA were similar to the method described by Knight et al (2003). The GLC analyses for milk used a BPX 70 column with a column of 10 m length, 0.1 mm internal diameter, and 0.1 (Am thickness with an injection volume of 0.1 |Al, whereas for plasma, a column of 30 m length, 0.32 mm internal diameter, and 0.25 (Am thickness with an injection volume of 1 | Al was used.…”
Section: Saponification Methylation and Glc Analysismentioning
confidence: 94%
See 3 more Smart Citations